Pengaruh Manajemen Laba Terhadap Efisiensi Bank Konvensional Di Indonesia - Sari, Dela Puspita (Jurnal Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
The most important aspect, which is the main focus in performance measurement, is efficiency in order to reduce operational costs. The purpose of this study is to analyze the effect of earnings management on the efficiency of conventional banking in Indonesia. This research uses a quantitative approach with a population of conventional commercial banks in 2019–2022. And for the collection of samples, a purposive sampling method with a non-probability sampling technique is used. From the sample criteria, the sample results are obtained, namely the annual report of 10 conventional commercial banks in 2019–2022, with a total of 40 data points. The methods used are DEA for measuring the level of efficiency and simple linear regression for hypothesis testing with SPSS software. The results of hypothesis testing show that there is a significant negative effect of earnings management on the efficiency of conventional banks